Exploitation of native microflora of Darjeeling hills for sclerotial rot management and growth promotion in pulses - and B.N. CHAKRABORTY*, K. SUNAR, U. CHAKRABORTY (Indian Phytopathology, 2014)
Isolation of microorganisms from various forest, riverine and rhizosphere soils of Darjeeling hills yielded 357 fungi and 135 bacteria. A large number of potential biocontrol agents (BCA) were obtained, among them Trichoderma harzianum and Talaromyces flavus showed suppression to a wide range of fungal pathogens under in vitro. Phosphate solubilizing fungi viz. Aspergillus niger, A. clavatus, A. melleus and T. flavus could enhance growth of Glycine max, Phaseolus vulgaris and Cicer arietinum with significant increase in soil phosphatase activity. Among the bacterial isolates, Bacillus pumilus (BRHS/C-1) was designated as the most potential PGPR which could solubilize phosphate, produce IAA, HCN as well as inhibit phytopathogens to a higher extent compared to other isolates. B. pumilus was also found to enhance growth of legumes in field conditions. Both the BCA and PGPR could inhibit sclerotial rot of Vigna radiate and Glycine max caused by Sclerotium rolfsii in pot conditions. These microorganisms elicited induced systemic resistance against the pathogen by enhancing key defense enzymes like chitinase, Î²1-3 glucanase, peroxidase and phenylalanine ammonia lyase when applied prior to pathogen challenge.